Evaluasi Pembelajaran AR Sejarah Berbasis SUS, UEQ, TAM - Rudi Kurniawan; Dadang Sudrajat; Kaslani; Gifthera Dwilestari; Sandy Eka Permana (Prosiding SISFOTEK, 2025)
History education in secondary schools still faces challenges in presenting material that attracts the digital generation’s attention. The Bandung Lautan Api event, a topic rich in local and national values, is often taught using conventional methods that limit student engagement and motivation. This study evaluates the feasibility of Augmented Reality (AR)-based learning media to enhance students’ historical literacy on the Bandung Lautan Api topic. A quantitative approach was applied using three integrated evaluation models: the System Usability Scale (SUS), User Experience Questionnaire (UEQ), and Technology Acceptance Model (TAM), involving 100 respondents comprising high school teachers and students. The results indicate that the AR media demonstrates excellent usability (SUS = 87.69), a highly positive user experience across all UEQ dimensions (highest attractiveness = 2.12), and strong technology acceptance (PU = 5.87; PEOU = 5.69; BI = 6.18). Both teachers and students shared consistent perceptions. These findings confirm that the AR media is feasible and capable of creating immersive and interactive learning experiences. Theoretically, this research enriches AR-based learning evaluation literature, while practically, it provides a ready-to-adopt model for integrating AR into history education.